On a class of nonvariational problems in fractional Orlicz–Sobolev spaces. (January 2020) - Bahrouni, Anouar; Bahrouni, Sabri; Xiang, Mingqi
Abstract: In this paper, we deal with a nonlinear problem driven by the fractional M -Laplacian and with a nonlinear nonhomogeneous reaction term. First, we give some further properties for the new fractional Orlicz–Sobolev space. Then, using the theory of nonlinear operators of monotone-type, we show the existence of a nonnegative solution. Our problem is nonvariational in nature.